THE DEVELOPMENT OF PERFORMANCE-BASED HIGH SCHOOL FINANCING MANAGEMENT MODEL OF SENIOR-HIGH SCHOOLS IN PEMALANG REGENCY - Cheristiyanto, Cheristiyanto; Sugiyo, Sugiyo; Slamet, Achmad; Hardyanto, Wahyu (Universitas Negeri Semarang, 2017)
Three main resources of school financial management problem in Indonesia are (a) the low transparency and accountability (b) the inappropriate standard operating procedures (SOP), and (c) the inappropriate operational fund calculating system. This research aims to develop the school financial management system. This is a research and development (R&D) which implemented three main steps, i.e. (a) describing the school financial management system, (b) developing a model, and (c) validating the model. The subjects of the study were two state senior high schools in Pemalang regency. There are three main results of this research. They are the real description of the school financial management system, the model or SOP for financial management, and the model for calculating the school operational fund. After being validated, the models were proven effective.